Geometry of vectorial martingale optimal transportations and duality - Lim, Tongseok (Mathematical programming, 2024)
The theory of Optimal Transport and Martingale Optimal Transport (MOT) were inspired by problems in economics and finance and have flourished over the past decades, making significant advances in theory and practice. MOT considers the problem of pricing and hedging of a financial instrument, referred to as an option, assuming its payoff depends on a single asset price. In this paper we introduce Vectorial Martingale Optimal Transport (VMOT) problem, which considers the more general and realistic situation in which the option payoff depends on multiple asset prices. We address this problem of pricing and hedging given market information—described by vectorial marginal distributions of underlying asset prices—which is an intimately relevant setup in the robust financial framework. We establish that the VMOT problem, as an infinite-dimensional linear programming, admits an optimizer for its dual program. Such existence result of dual optimizers is significant for several reasons: the dual optimizers describe how a person who is liable for an option payoff can formulate optimal hedging portfolios, and more importantly, they can provide crucial information on the geometry of primal optimizers, i.e. the VMOTs. As an illustration, we show that multiple martingales given marginals must exhibit an extremal conditional correlation structure whenever they jointly optimize the expectation of distance-type cost functions.